Detection and clinical significance of DNA repair gene ERCC8 tag SNPs in gastric cancer - Lu, Xingre; Chen, Fengyu; Liu, Xiaowen; Yuan, Diao; Zi, Yunju; He, Xiang; Zhu, Deyong (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Excision repair cross-complementing group 8 (ERCC8) is one of the members of the nucleotide excision repair pathway. This study aimed to explore the association between ERCC8 tag single nucleotide polymorphisms (SNPs) and gastric cancer. Materials and Methods: Totally, 120 patients with gastric cancer treated from March 2010 to March 2011 were selected as the observation group and 120 healthy individuals were selected as the control group during the same period. The Sequenom MassARRAY system was used to identify genotypes in these samples. The genetic locus of ERCC8 tag SNPs and the relevance of gastric cancer risk to the different ERCC8 genotypes alone or in combination with Helicobacter pylori infection were observed and analyzed. The AA, GA, and GG genotypes on rs158572 and rs158916 in the observation and control groups were compared. Results: The results showed that the odds ratio of the different ERCC8 rs158572 and rs158916 genotypes was not significantly increased in the observation group compared with that in the control group. By contrast, in patients with H. pylori infection, the ERCC8 rs158572 GA/GG and rs158916 TT genotypes showed a 7.921-fold and 8.021-fold [95% confidence interval (CI)=4.022-15.921, p=0.029 and 95% CI=3.021-15.092, p=0.021, respectively] increased risk of gastric cancer than the AA and CT/CC genotypes, respectively. Conclusion: Helicobacter pylori infection combined with ERCC8 rs158572 and rs158916 can be used as a predictive index of gastric cancer occurrence. Cite this article as: Lu X, Chen F, Liu X, et al. Detection and clinical significance of DNA repair gene ERCC8 tag SNPs in gastric cancer. Turk J Gastroenterol 2018; 29: 392-6.